A Positive Doctrine of Tyranny? The Rule of Law Vs. The Rule of a Tyrant in Archaic and Classical Greece. (2022) - Joyce, Christopher J.
Abstract: The origins and definition of tyranny in ancient Greece have been debated in scholarship for well over three quarters of a century. Recently, it has been argued that tyranny as a political idea was not anathematised until late and that in the fifth century BCE and before, tyranny comported no negative judgment. While correct to point out that the distinction between 'king' and 'tyrant' in literature predating Aristotle was not clearly delineated, scholars have often failed to ask the more fundamental question of why that distinction was essential for Aristotle. This essay argues that Aristotle drew upon a much older intellectual tradition which saw tyranny as hateful and contrary to the rule of law. Though tyrants in many cases ruled lawfully, a distinction must be drawn between 'lawful' rule, which some but not all tyrants practised, and the rule of law, which anathematised tyranny.